Custom order entry for Parkinson’s medications in the hospital improves timely administration: an analysis of over 31,000 medication doses - Azmi, Hooman; Cocoziello, Lisa; Ruzicka, Francis; Clar, Elana; Pederson, John Michael; Jacob, Blessy; Thomas, Jewell; Rocco, Anthony; Bobek, Mary; Pereira-Argenziano, Lucy; Roth, Patrick; Thomas, Florian P. (Frontiers in Aging Neuroscience, 2023)
Background Patients with Parkinson’s disease (PD) are at increased risk for hospital acquired complications. Deviations from home medication schedules and delays in administration are major contributing factors. We had previously developed a protocol to ensure adherence to home medication schedules using “custom” ordering. In this study we are assessing the impact this order type may have on reducing delays in PD medication administration in the hospital. Material and methods We reviewed 31,404 orders placed for PD medications from January 2, 2016 to April 30 2021. We evaluated the orders to determine if they were placed in a Custom format or using a default non-custom order entry. We further evaluated all orders to determine if there was a relationship with the order type and timely administration of medications. We compared medications that were administered within 1 min, 15 min, 30 min and 60 min of due times across custom orders vs. non-custom default orders. We also evaluated the relationship between ordering providers and type of orders placed as well as hospital unit and type of orders placed. Results 14,204 (45.23%) orders were placed using a custom schedule and 17,200 (54.77%) orders were placed using non-custom defaults. The custom group showed a significantly lower median delay of 3.06 minutes compared to the non-custom group (p<.001). Custom orders had a significantly more recent median date than non-custom default orders (2019-10-07 vs. 2018-01-06, p<0.001). In additional analyses, medication administration delays were significantly improved for custom orders compared to non-custom orders, with likelihoods 1.64 times higher within 1 minute, 1.40 times higher within 15 minutes, and 1.33 times higher within 30 minutes of the due time (p<0.001 for all comparisons). Conclusion This is the largest study to date examining the effects of order entry type on timely administration of PD medications in the hospital. Orders placed using a custom schedule may help reduce delays in administration of PD medications.